Molecular Hydrogen Mitigates Performance Decrement during Repeated Sprints in Professional Soccer Players - Botek, Michal; Khanna, Deepesh; Krejčí, Jakub; Valenta, Michal; McKune, Andrew; Sládečková, Barbora; Klimešová, Iva (Nutrients, 2022)
Hydrogen-rich water (HRW) supplementation has been shown to have an antifatigue effect across different modes of exercise. However, its effect on repeated sprint performance is unknown. The aim of this study was to assess the effect of pre-exercise HRW consumption on repeated sprint performance, lactate, and perceptual responses using a repeated sprint protocol. This randomized, double blinded, placebo controlled, crossover study included 16 professional, male soccer players aged 18.8 ± 1.2 years. Athletes performed two indoor tests, particularly 15 × 30 m track sprints interspersed by 20 s of recovery, separated by a 1-week washout period. Sprint time was measured at 15 m and 30 m. Ratings of perceived exertion were assessed immediately after each sprint, and post-exercise blood lactate concentration was measured after the last sprint. There were significantly faster sprint times after HRW consumption compared with placebo at 15 m for the 14th and 15th sprints, representing improvements in time of 3.4% and 2.7%, respectively. Sprint time at 30 m also significantly improved by 1.9% in the HRW group in the last sprint. However, neither lactate concentrations nor ratings of perceived exertion were significantly different between HRW and placebo. Pre-exercise HRW supplementation is associated with an increased ability to reduce fatigue, especially during the later stages of repeated sprint exercise.
Keywords: dospělí; klinické křížové studie; vodík; Adult; mladý dospělý; Lactic Acid; Adolescent; kyselina mléčná; Soccer; běh; lidé; Athletic Performance; Cross-Over Studies; fotbal; Running; Hydrogen; Male; Young Adult; sportovní výkon; mužské pohlaví; mladiství; Humans